Party influence in Congress - Smith, Steven S. 1953- (Cambridge University Press, 2007)
Party Influence in Congress challenges current arguments and evidence about the influence of political parties in the US Congress. Steven S. Smith argues that theory must reflect policy, electoral, and collective party goals. These goals call for flexible party organizations and leadership strategies. They demand that majority party leaders control the flow of legislation; package legislation and time action to build winning majorities and attract public support; work closely with a president of their party; and influence the vote choices for legislators. Smith observes that the circumstantial evidence of party influence is strong, multiple collective goals remain active ingredients after parties are created, party size is an important factor in party strategy, both negative and positive forms of influence are important to congressional parties, and the needle-in-the-haystack search for direct influence continues to prove frustrating